2015
DOI: 10.1136/bcr-2014-208633
|View full text |Cite
|
Sign up to set email alerts
|

Testicular non-Hodgkin's lymphoma presenting in a young adult

Abstract: SUMMARYWe report a case of a 27-year-old man who presented with a slowly growing left testicular swelling associated with mild pain over a period of 3 months. He was evaluated by his family physician with scrotal ultrasound and testicular tumour markers. He was diagnosed and treated as epididymo-orchitis and managed with antibiotics. When he later presented to us, he had an enlarged left testis with normal spermatic cord. Scrotal Doppler evaluation showed a globally enlarged left testis and epididymis with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…To our knowledge, there are four reports 3,12,14,18 of testicular lymphoma presenting as epididymo-orchitis. In another report by Mazzu et al, 11 one patient had enlarged hypervascular epididymis but the presence of epididymal inflammation without histological correlation was suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there are four reports 3,12,14,18 of testicular lymphoma presenting as epididymo-orchitis. In another report by Mazzu et al, 11 one patient had enlarged hypervascular epididymis but the presence of epididymal inflammation without histological correlation was suggested.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Familiarity with US features of testicular lymphoma will help to differentiate lymphoma from other germ cell tumours or inflammation and provide appropriate management. Since reports of US features of testicular lymphoma remain limited, 3,[7][8][9][10][11][12][13][14][15][16][17][18][19] we reviewed the clinical presentation and US features of testicular lymphoma at our institution to add to the current knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The most common clinical manifestation of this entity is a unilateral painless testicular swelling, with a frequent vascular invasion, epididymis and cord involvement [9]. The disease tends to relapse promptly after initial management involving orchiectomy and chemoradiotherapy [10].…”
Section: Discussionmentioning
confidence: 99%
“…6 It is well-known that testicular lymphoma is more common among patients over 60 years of age, and rarely encountered in younger patients. 7 Secondary testicular lymphoma is more common in patients under 60 years of age and bilateral testicular involvement is more common. Bertalotto et al reported that 75% of 43 patients with testicular lymphoma were over the age of 60 at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%